2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5649223
|View full text |Cite
|
Sign up to set email alerts
|

Vision based victim detection from unmanned aerial vehicles

Abstract: Abstract-Finding injured humans is one of the primary goals of any search and rescue operation. The aim of this paper is to address the task of automatically finding people lying on the ground in images taken from the on-board camera of an unmanned aerial vehicle (UAV).In this paper we evaluate various state-of-the-art visual people detection methods in the context of vision based victim detection from an UAV. The top performing approaches in this comparison are those that rely on flexible part-based represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 29 publications
0
70
0
Order By: Relevance
“…Notably prior work does not address autonomy within this context [19,20] and work considering multi-modal detection is in its infancy [7,17,18]. Of those aerial techniques addressing autonomous target detection most borrow heavily from the state of the art in generalised object detection such as [7,17,21,22] but with often aerial detection specific enhancements (e.g. [7,22]).…”
Section: Introductionmentioning
confidence: 99%
“…Notably prior work does not address autonomy within this context [19,20] and work considering multi-modal detection is in its infancy [7,17,18]. Of those aerial techniques addressing autonomous target detection most borrow heavily from the state of the art in generalised object detection such as [7,17,21,22] but with often aerial detection specific enhancements (e.g. [7,22]).…”
Section: Introductionmentioning
confidence: 99%
“…This system functioned efficiently during disaster response and provided efficient data fusion from its sensor suite. Andriluka et al (2010) showed that vision-based human detection algorithm from UAV imagery produced feasible workflows combining various computer vision detectors such as pictorial structures (Andriluka et al, 2009) and discriminately trained models (Felzenszwalb et al, 2009), similar to components of Support Vector Machine (SVM). Rudol et al, (2008) introduced human body detection via positioning algorithms using visible and infrared imagery.…”
Section: State-of-the-art Geospatial Data Acquisition and Processing mentioning
confidence: 99%
“…In a different way Andriluka et al (2010) evaluate various existing detection methods for detecting victims at nearby distances. According to this study, part-based detectors are better suited for victim detection from a UAV because they natively take into account the articulation of the human body.…”
Section: Existing Work For Detecting Human From the Airmentioning
confidence: 99%